Astragaloside attenuates lipopolysaccharide‐induced cell apoptosis in human gingiva cells via MAPK signaling pathway. Issue 8 (18th April 2019) - Shen, Xionghu; Sun, Honghua; Cui, Hai; Jin, Yongmin; Jin, Wenbo; Cui, Xian; Guo, Jie
Abstract: Subjects: The aim of this study was to research the antiapoptotic effect of astragaloside, the principal component of Astragalus membranaceus (Fisch) Bge, in human gingiva cells induced by lipopolysaccharide (LPS). Methods: According to the treatment, human gingiva cells were divided into five groups, including (1) control group without drug treatment; (2) imitating group, treated with LPS (10 μg·mL −1 ) alone; (3) low group, treated with LPS and 50 μmol·L −1 astragaloside; (4) medium group, treated with LPS and 100 μmol·L −1 astragaloside; and (5) high group, treated with LPS and 150 μmol·L −1 astragaloside. Cell proliferation and apoptosis were investigated using MTT assay and flow cytometry, respectively. Apoptosis and mitogen‐activated protein kinase associated proteins were determined using Western blot analysis. Results: LPS significantly suppressed the proliferation of human gingiva cells, but astragaloside obviously attenuated this change with a dose‐dependent manner. LPS significantly promoted the apoptosis of human gingiva cells, but astragaloside treatments significantly attenuated this change with a dose‐dependent manner. In addition, LPS could significant upregulated the expression of P‐p38, P‐JNK, Bax, and caspase‐3. Conclusion: Astragaloside preformed a promising antiapoptotic role in apoptosis of human gingiva cells induced by LPS. This finding might provide us with a novel therapeutic method in tooth protection. Abstract : Astragaloside preformed a promising antiapoptotic role in apoptosis of human gingiva cells induced by LPS. This finding might provide us with a novel therapeutic method in tooth protection.